2014
DOI: 10.1007/s00421-013-2806-5
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced oxidative stress and hypoxic exercise recovery

Abstract: Hypoxia due to altitude diminishes performance and alters exercise oxidative stress responses. While oxidative stress and exercise are well studied, the independent impact of hypoxia on exercise recovery remains unknown. Accordingly, we investigated hypoxic recovery effects on post-exercise oxidative stress. Physically active males (n = 12) performed normoxic cycle ergometer exercise consisting of ten high:low intensity intervals, 20 min at moderate intensity, and 6 h recovery at 975 m (normoxic) or simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 39 publications
4
33
0
1
Order By: Relevance
“…A follow-up study by our group was performed where subjects exercised at 975m with recovery in a hypoxic environment. Findings from the follow-up investigation reveal that normoxic exercise followed by hypoxic recovery attenuate the post exercise peak in plasma LOOH (Ballmann et al, 2014). Further investigation using multiple recovery altitudes confirmed that this finding in recovery is altitude-dependent (unpublished).…”
Section: Plasma Oxidative Damage Biomarkerssupporting
confidence: 71%
See 1 more Smart Citation
“…A follow-up study by our group was performed where subjects exercised at 975m with recovery in a hypoxic environment. Findings from the follow-up investigation reveal that normoxic exercise followed by hypoxic recovery attenuate the post exercise peak in plasma LOOH (Ballmann et al, 2014). Further investigation using multiple recovery altitudes confirmed that this finding in recovery is altitude-dependent (unpublished).…”
Section: Plasma Oxidative Damage Biomarkerssupporting
confidence: 71%
“…Other studies investigating ultra-marathon distances support an increase in plasma FRAP postexercise (Nieman et al, 2003;Quindry et al, 2008). Interestingly, current findings from our laboratory show that recovery from an identical exercise protocol, when performed in a hypoxic environment (5000 m) resulted in a decrease in plasma FRAP and TEAC compared with normoxic recovery (Ballmann et al, 2014). …”
Section: Plasma Antioxidant Capacity Biomarkersmentioning
confidence: 64%
“…Gene expression of Nrf2 and target SOD2 were shown to increase significantly in skeletal muscle of young fit males following an acute bout of cycling exercise lasting 90-min in normoxic recovery conditions [47]. Interestingly, these responses were not seen when recovery was performed under hypoxic conditions [47]. Similarly Nrf2 mRNA was significantly increased at 2-h post 30-min of moderate treadmill exercise in middle-aged women who were regular exercisers; however, sedentary women showed no change in gene expression for Nrf2 or targets in response to the exercise bout [48], suggesting that fitness may play a role in maintaining the acute Nrf2 response with aging.…”
Section: Nrf2 Signaling In Response To Acute Exercisementioning
confidence: 99%
“…Gene expression of Nrf2 and target SOD2 were shown to increase significantly in skeletal muscle of young fit males following an acute bout of cycling exercise lasting 90-min in normoxic recovery conditions [47]. Interestingly, these responses were not seen when recovery was performed under hypoxic conditions [47].…”
Section: Nrf2 Signaling In Response To Acute Exercisementioning
confidence: 99%
“…Blood is the most common for exercise-induced oxidative stress and biomarker extraction. Biomarkers present in blood include protein carbonyls [83,84,85,86]; total antioxidant capacity [87,88]; F 2 -isoprostanes [89,90]; malondialdehyde [91]; and Thiobarbituric Acid-Reactive Substances (TBARS), of malondialdehyde [92,93]. The presence of such blood biomarkers does not necessarily indicate damage is occurring in the surrounding cells/tissues; malondialdehyde, for instance, can be a product of actual damaged-tissue but also a product of reactive species.…”
Section: Oxidative Stress and Free Radicalsmentioning
confidence: 99%